Day 3 Thu, October 14, 2021 2021
DOI: 10.2118/205569-ms
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Stable Specific Enzyme for Guar Polymer Based Fracturing Fluid Degradation

Abstract: Hydraulic fracturing, commonly referred to as fracking, is a widely used technology to enhance the productivity of low-perm reservoirs and the aqueous-based fracturing fluids use guar as the rheology builder. Residual polymer layer over the fractured surface results in a reduced matrix to fracture permeability, causing reduced well productivity. This research aims to develop a specialized mannanase enzyme and evaluate its efficiency in degrading linear and cross-linked guar polymer gel as a function of time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…71 Abdelrahim et al studied the damage of the residual fracturing fluid to the core through the coreflooding experiment. 72 The results indicated that the residual fracturing fluid may reduce the permeability of brine injection by 99% or more. Even after 48 h of aging and back-flowing, the oil recovery permeability significantly still decreased.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 97%
See 1 more Smart Citation
“…71 Abdelrahim et al studied the damage of the residual fracturing fluid to the core through the coreflooding experiment. 72 The results indicated that the residual fracturing fluid may reduce the permeability of brine injection by 99% or more. Even after 48 h of aging and back-flowing, the oil recovery permeability significantly still decreased.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 97%
“…The retained permeability of the metal-cross-linked synthetic polymer fluid tested by Lee et al with a temperature resistance of up to 232 °C is less than 80% . Abdelrahim et al studied the damage of the residual fracturing fluid to the core through the core-flooding experiment . The results indicated that the residual fracturing fluid may reduce the permeability of brine injection by 99% or more.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…Most fracturing fluids use an optimum dose of guar-based polymers (guar and its derivatives). The guar derivatives most commonly used in fracturing fluids include carboxymethyl guar (CMG), hydroxypropyl guar (HPG), and carboxy Methyl hydroxypropyl guar (CMHPG), with each having unique properties [23]. It is of paramount interest to select the correct type of guar at an optimized concentration when designing fracture treatments to deal with the rheology and temperature constraints.…”
Section: Frac Fluids and Their Propertiesmentioning
confidence: 99%
“…These modified guar derivatives gained popularity because of their unique properties, such as high molecular weight (ranging from 1 to 2 MD), helping to generate high viscosity at low concentration, quick hydration, stability at a higher temperature, and a greater pH range (pH 4.5-10). They also crosslink with metals, biocompatible, biodegradable, and non-toxic nature [23].…”
Section: Water-based Gelled Fluidsmentioning
confidence: 99%
See 1 more Smart Citation